Structural Safety Analysis of Pahlawan University Apartment Building - Khoiri, Pastabiqul; Setiawan, Beny; Musridho, R. Joko (Journal of Engineering Science and Technology Management, 2026)
The Rusunawa Putri Building at Universitas Pahlawan serves as a student residence operating 24 hours a day, providing essential accommodation facilities. Current physical conditions show several damages, including wall cracks, water seepage, damaged doors, and ceiling deterioration. This study aims to identify the factors influencing building reliability and to assess the reliability level of the Rusunawa Putri Building. A descriptive quantitative and qualitative method was applied, involving field observations, interviews, and questionnaires distributed to 28 residents. The assessment refers to the Ministry of Public Works Regulation No.29/PRT/M/2006, which includes five aspects: architecture, structure, utilities and fire protection, accessibility, and building and environmental layout. The findings show reliability values of 75% for architecture, 78% for structure, 82% for utilities and fire protection, 76% for accessibility, and 76% for building and environmental layout. Overall, the building achieved a reliability score of 82%, which falls into the less reliable category (75–<95%). This study recommends periodic maintenance and the provision of essential components such as hydrants, sprinklers, evacuation facilities, and disability-accessible amenities to improve building safety and reliability